On writing well : an informal guide to writing nonfiction - Zinsser, William Knowlton. 4 0 16; 5 (New York : Harper and Row, 1980)
Provides advice on writing about science, sports, travel, and other nonfiction subjects.
Includes bibliographical references and index.
Young Adult;Young Adult
Keywords: 2 -- 0; 6; Rhetoric. -- English language;Exposition (Rhetoric) -- 20; 20; 2